Mirror-touch synesthesia in schizophrenia, a pathological condition? - César Augusto Trinta Weber; Mario Francisco Pereira Juruena (Debates em Psiquiatria, 2022)
Introduction: The mirror-touch synesthesia is a condition where a touch perception in another person's body induces the person who is observed to feel being touched in the same way. Case report: A single 22-year-old man came to the medical appointment in a private psychiatric clinic. Since his adolescence, he refers to auditive hallucinations, pseudo-hallucinations, frequent persecutory delusions, sonorization and insertion of the thought, and synesthesia. Among them it was reported mirror-touch synesthesia, anhedonia, and abulia. The criteria for paranoid schizophrenia were achieved during the examination. Discussion: Some evidence suggests that schizotypy may be associated with mirror-touch synesthesia. Conclusion: Scientific articles that demonstrate mirror-touch synesthesia as a part of pathology were not found.